Design and Construction of Water Heater with Induction Method with Arduino Uno Monitoring - Achmad Karim Fadhillah; Arief Wisaksono (Procedia of Engineering and Life Science, 2022)
Induction heating is a process in which the heater and the object to be heated are not in physical contact. Therefore, several previous studies did not provide information about the effect of winding and coil diameter on the performance of induction heaters. The sensor used is the Ds18b20 sensor which detects the temperature of hot water and cold water. To increase the effectiveness of the use of heat energy through an induction heater directly, the research tool is an induction water heater. Induction heating is the generation of heat in a metal exposed to an induced magnetic field. In this process, a validated graphic temperature controller is invaluable through the monitoring process using software that can detect the hot temperature of the Blynk and 16X2 LCD. The hot water temperature generated by the induction heater allows the system to operate optimally. As a result, the capillary tube reaches a hot temperature and a constant water temperature of 38 ° C in 173 seconds. The microcontroller and flash connection detection test is working fine. This system makes it easy to carry out the temperature monitoring process via a smartphone.